2012
DOI: 10.1007/s00438-012-0719-3
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide analysis and expression profiling of half-size ABC protein subgroup G in rice in response to abiotic stress and phytohormone treatments

Abstract: The roles of the proteins encoded by half-size adenosine triphosphate-binding cassette transporter subgroup G (ABCG) genes in abiotic stress responses are starting to be established in the dicot model Arabidopsis thaliana. In the monocot model rice, the functions of most half-size ABCG proteins in abiotic stress responses are unknown. Rcn1/OsABCG5 is an essential transporter for growth and development under abiotic stress, but its molecular function remains largely unclear. Here, we present a comprehensive ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 48 publications
1
22
0
Order By: Relevance
“…A total of 995 proteins (Additional file 1 : Table S1) containing one or more ATP-binding cassette domains were identified. Our analysis enlarged number of ABC proteins identified in rice [ 13 ], confirming data on ABCG family refined by Matsuda et al [ 14 ], added 32 novel ABC transporters in V. vinifera , [ 15 ] and provide manual curated ABC protein catalogues for S. lycopersicum, S. tuberosum. Most of these proteins belong to known plant subfamilies (A-I, except H) (Additional file 2 : Table S2 and Additional file 3 ).…”
Section: Resultssupporting
confidence: 82%
“…A total of 995 proteins (Additional file 1 : Table S1) containing one or more ATP-binding cassette domains were identified. Our analysis enlarged number of ABC proteins identified in rice [ 13 ], confirming data on ABCG family refined by Matsuda et al [ 14 ], added 32 novel ABC transporters in V. vinifera , [ 15 ] and provide manual curated ABC protein catalogues for S. lycopersicum, S. tuberosum. Most of these proteins belong to known plant subfamilies (A-I, except H) (Additional file 2 : Table S2 and Additional file 3 ).…”
Section: Resultssupporting
confidence: 82%
“…ABC proteins are primary transporters that mediate the energy-driven transport of a large and diverse multitude of substrates across biological membranes. ABC transporters play key roles in many physiological processes, such as plant development and plant nutrition, and in stress response (Moons 2008 ; Matsuda et al 2012 ; Jarzyniak and Jasinski 2014 ; Nguyen et al 2014 ; Saha et al 2015 ). In the rice genome, 133 genes coding for ABC transporters have been identified (Saha et al 2015 ).…”
Section: Resultsmentioning
confidence: 99%
“…In our study, in 3 h-treated roots, 15 out of the 133 ABC transporter genes were modulated in the same way in the two cultivars, 4 and 7 ABC transporter genes were specifically up-regulated in Eurosis and Loto, respectively, and 14 and 3 ABC transporter genes were specifically down-regulated in Eurosis and Loto, respectively. Among the 4 Eurosis-specific up-regulated genes, the OsABCG22 gene (LOC_Os09g29660) is induced by mannitol and by ABA treatments in rice roots (Matsuda et al 2012 ). Moreover, Nguyen et al ( 2014 ) found that drought stress induced this gene in the leaves.…”
Section: Resultsmentioning
confidence: 99%
“…There have been many other whole transcriptome microarray studies in rice under different abiotic stress conditions, but they reported only specific gene families that responded to various stresses. They include the MADS-box transcription factor family (Arora et al, 2007 ), F-Box Proteins (Jain et al, 2007 ), calcium-dependent protein kinase (CDPK) gene family (Ray et al, 2007 ), auxin-responsive genes (Jain and Khurana, 2009 ), protein phosphatase gene family (Singh et al, 2010 ), Sulfotransferase (SOT) gene family (Chen et al, 2012 ), thioredoxin gene family (Nuruzzaman et al, 2012 ), half-size ABC protein subgroup G (Matsuda et al, 2012 ), class III aminotransferase gene family (Sun et al, 2013 ), Ca 2+ ATPases gene family (Kamrul Huda et al, 2013 ), Rice RING E3 Ligase Family (Lim et al, 2013 ) etc.…”
Section: Introductionmentioning
confidence: 99%